Blood Pressure and Sodium Consumption: A Study of Fast Food Workers in Central Jakarta - Lestari, Adni Ageng; Razaq, Asa Azkatu; Soekatri, Moesijanti Y.E. (Poltekita: Jurnal Ilmu Kesehatan, 2024)
This study aimed to investigate the relationship between blood pressure and the frequency of consuming sodium-rich foods among employees of a western-style fast food restaurant "X" in Hayam Wuruk, Central Jakarta. A cross-sectional study was conducted with 30 respondents aged 20-50 years, selected using purposive sampling. Data on respondent characteristics, blood pressure, and frequency of consuming sodium-rich foods were collected using questionnaires and a food frequency questionnaire (FFQ). The results showed that prehypertension and stage 1 hypertension were more prevalent in respondents who had worked for ≤ 3 years (76.7%), were aged 19-29 years (76.7%), were male (56.7%), had a high school education (96.7%), and rarely consumed sodium-rich foods (43.3%). However, no significant associations were found between blood pressure and duration of working time, sex, age, or frequency of consuming sodium-rich foods (p>0.05). The most frequently consumed sodium-rich foods were chicken eggs, butter, margarine, beef meatballs, chicken noodles, fried tempeh, and bakwan. The prevalence of hypertension in this study (6.7%) was lower than that reported in the 2018 Basic Health Research (Riskesdas) data for Central Jakarta (39.05%). The study's limitations include the focus on a single fast food restaurant and the small sample size. The findings suggest that restaurant employees should avoid high-sodium foods and monitor their blood pressure regularly.